Digitally-delivered cognitive-behavioural therapy for youth insomnia: A systematic review - Aliza Werner-Seidler; Lara Johnston; Helen Christensen (Internet Interventions, 2018)
Sleep disturbance is common among young people, with consequences for academic, emotional and behavioural development. Cognitive-behavioural therapy for insomnia (CBT-I) is efficacious, yet it is costly and not available to many who need it. Digitally-delivered CBT-I (eCBT-I) has the potential to overcome these barriers. The purpose of this systematic review was to identify studies which report on the efficacy or effectiveness of eCBT-I for young people with sleep disturbance. Electronic databases were systematically searched and three studies met inclusion criteria. Two studies used the same online intervention for adolescents with insomnia symptoms, while the other was conducted in a college sample of individuals who opted into a stress-management study. Results showed that eCBT-I improved sleep efficiency, sleep quality, sleep-onset latency and total sleep time with effect sizes ranging from 0.17–1.30 (Cohen's d). This suggests that eCBT-I is a promising intervention for young people, but more studies are needed to verify the conditions under which it is most effective.